Konsep Akhlak dalam Kitab Adabul ‘Alim Wal Muta’allim dan Implementasinya pada Pembinaan Akhlak Santri - Hesti Winingsih; Imam Syafe'i; Ahmad Fauzan; M. Kharis Fadilah (Fitrah: Journal of Islamic Education, 2022)
The study aimed to analyze the concept of morality in the book Adabul 'Alim wal Muta'allim and its implementation in fostering the morals of the students of the Roudlotut Tholibin Metro Islamic Boarding School. This study uses a qualitative research method with a narrative study approach. Primary data sources consist of library sources, namely the book Adabul 'Alim wal Muta'allim written by K.H. Hasyim Asy'ari and research informants, namely kiai and santri. Collecting data using observation techniques, interviews, and documentation studies. Data analysis uses data reduction flow, data presentation, and drawing conclusions The results of the study revealed that the implementation of the book Adabul 'Alim Wal Muta'aliim in fostering the morals of students is realized by: (1) enactment of rules and regulations that require students to participate in all non-formal activities in the form of reciting books at madrasah diniyah and formal education at schools ; (2) the independence of the santri in managing all daily activities starting from waking up, performing ablutions, praying in congregation, eating, bathing, washing clothes, maintaining cleanliness; (3) the habit of speaking politely to teachers and elders; (4) helping the kiai carry out the work and meet the daily needs of the santri.